The Role of Employee Well-Being as A Moderator: Job Crafting and Work Engagement - Wardani, Laila Meiliyandrie Indah; Apriliani, Adlin; Riskinanti, Karisma; Dearly, Dearly; Sharif, Sabariah Bte (Universitas Muhammadiyah Surakarta, 2023)
Abstract. New normal is a new adaptation carried out to deal with covid-19, where people are allowed to return to their activities in the field of work while still complying with health protocols. In the new normal situation, work engagement is a challenge for all companies. The purpose of this study is to determine whether job crafting has a relationship with work engagement and to determine whether employee well-being acts as a moderator between job crafting and employee work engagement in the new normal era. This study also examines whether gender issues are present in the variables. The subjects of this study were 533 employees in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) Indonesia. The instruments used in this study were the Utrecht Work Engagement Scale (UWES), the Job Crafting Scale (JCS), and the Employee Well-Being Scale (EWBS). This research design was conducted in moderation using multiple sampling technique and moderated regression analysis PROCESS V4.0 Procedure for SPSS model no. 1 by Andrew F. Hayes. The results of this study indicate that job crafting is positively correlated with work engagement, and employee well-being plays a moderating role in the relationship between job crafting and work engagement. Moreover, the results of this study indicate that male and female workers have different level of engagement at work and employee well-being. This research can cover the gap in previous research so that it is expected to be a literature material for employees and companies regarding the importance of understanding the values of work engagement, job crafting, and employee well-being for the company's success.Keywords: work engagement; well-being; job crafting; employee; new normal; gender